Heiner Müller e Brecht - Röhl, Ruth (In:Pandaemonium Germanicum;São Paulo : Humanitas Publicações, 1997-2006;Band 4, Heft 1 (2000), Seite 99-107;22 cm, 2000)
Based on Heiner Müller's play 'Fatzer +- Keuner', the present article shows Müller's opinion on Bertolt Brecht's work. The adaptations of Brecht's didactic plays (Lehrstücke) by Müller are commented on and compared to the originals. Gestützt auf Heiner Müllers 'Fatzer +- Keuner', zeigt dieser Artikel Müllers Meinung über Brechts Werk. Müllers Bearbeitungen von Brechts Lehrstücken werden mit dem Original verglichen und kommentiert.
urn:nbn:de:hebis:30:3-260177
Keywords: Online-Publikation; Brecht; Bertolt; Müller; Heiner; Rezeption